Life Cycle Inventory for Electric Energy System in Brazil. - Coltro, Leda
Goal, Scope and Background. The goal of this paper is to present the modeling of life cycle inventory (LCI) for electric energy production and delivery in Brazil for the reference year 2000 by application of ISO 14040. Site specific data along with sector production data have been combined to construct an energy production model, which has been applied to emissions estimation. Background data of all the inputs and outputs from the system have been inventoried as follows : gross electric energy generation, installed nameplate capacity, flooded area, losses, emissions to air/water, process waste, used fuel, efficiency and land use. Main Features. In Brazil, electricity is supplied to the various regions by an interconnected system composed of 418 electric companies, consisting of 389 hydraulic power plants and 29 thermal power stations. Due to this enormous number of companies, life cycle inventory for the electricity grid mix was developed on the basis of the following hierarchy : information received from companies (15), data from Brazilian Industrial Information System for the energy Sector (SEISE) and Brazilian Ministries. The functional unit was 1,000 MJ (278 kWh) of electricity distributed to electricity users. The main emissions from power stations, as well as those from fuel production, were investigated. The hydraulic process was not considered emission free a model was proposed where emissions of renewable CO2 and CH4 (hydro) are attributed to the degradation of plants submerged in the reservoir seats. Result. The production and distribution of 1,000 MJ of electricity by the interconnected system in Brazil requires approx. 1,600 MJ of process energy, 230 kg of water (evaporated at thermal plants), 116 m3 of waterflow through the turbines, 13 kg of coal, 5 kg of biotic reserves and 0.25 m2a of land use. Emissions related to the 1,000 MJ electricity distributed were 18 kg of non-renewable CO2, 17 kg of renewable CO2, 540 g of CH4, 575 g of NOx, 116 g of SO2, 149 g of CO, among others. Thermal power stations are the main contributors to these emissions, except for CH4, and renewable CO2 being contributions from coal production and hydraulic power plants, respectively. Conclusions. In spite of considering the emissions of CO2 and CH4 by the submerged plants in the flooded area of dams in hydropower stations, it has been shown that electric energy production is a very clean process due to the characteristics of the electric energy production in Brazil-93.5 percent hydraulic. This means 1,000 MJ of delivered electricity produces approx. 34 kg of CO2, being 18 kg (53 percent) of non-renewable CO2 emitted by fossil fuel burning at thermal power plants that participate with only 6.5 percent of the electric energy production in Brazil. This was the first tentative model to express electric energy generation and distribution in Brazil in terms of LCA. In future, a more detailed study should be made in order to improve this model. Outlook. A complementary paper will be produced in which future scenarios of the Brazilian electricity grid mix will be discussed, including possible alternatives to minimize the environmental impacts of hydropower plants.
Keywords: Brazil; Electricity; Energy; Environment; Inventory; Life cycle assessment (LCA).